Kartiranje biografij slovenskih književnikov - Perenič, Urška (Primerjalna književnost, 2013)
Literary scholarship has always shown an interest in spatial dimensions and extensions of biographies, but it ascribed them a specific value. Pioneers of literary geography from the German linguistic area (Siegfried Robert Nagel and Josef Nadler) were mostly interested in the local, regional, national, or provincial origins of the authors, which is second only to the title of the work when it comes to the most commonly mapped literary-historical information. The province or geographical space was understood as the humus orbasis from which the authors and also the spiritual or literary achievements originate. Such a deterministic view of the space/place eased overtime, becoming only one of the factors that influence the development of the literary culture. Scholars such as Horst Dieter Schlosser started addressing other spatially bound data; for example, places of education, career, travels, publishing, or networking. Consequently, the manners of mapping have also changed: from the simple charts covered with transparent paper displaying literary monuments to more complicated-though not necessarily more explicit-biographical displays using a wide variety of cartographic symbols (from point marks to graphically more representative cartographic symbols such as the quaver). As a result of a project whose goal is to map the biographies of prominent Slovenian men of letters, this paper returns to a more basic manner of displaying biographies, using, say, point and linear display. In this sense, it is closer to the attempts from the beginning of the twentieth century. However, by using modern GIS technologies the project models cartographic displays according to the latest cartographic guidelines. Moreover, unlike the 1980s attempts, the project emphasizes not individual trajectories, but, using corpus processing, the literary culture from the beginnings of Slovenian aesthetic production. This enables not only new findings about the spatial development of Slovenian literature, but also certain generalizations of these findings. The structure of the entry mask for biographies, which was constructed for the purposes of this project, is accordingly differentiated and in principle enables the collection and visualization of all spatially bound and statistically relevant literary-historical data. Thematic maps designed as analytical tools for a spatial analysis of literature will focus on individual objects, displaying the following spatially linked components of biographies: 1) the network of birthplaces; 2) the network of the places of death; 3) the network of secondary school locations; 4) the network of secondary schools, which belong to the wider context of literary culture; 5) career paths that must be considered when verifying the modes of mobility of the men of letters and the spatial extent of literary culture; 6) the density of literary networks; 7) the print media and presses that participated in consolidating literary activity; and 8) individual literary memorial events. The article introduces the first thematic maps that are the results of the pilot project and the second phases of the project.
Keywords: Slovene literature; slovenska književnost; literarna kartografija; metodologija literarnega kartografiranja; analitični tematski zemljevidi; literarni sistem; literarna kultura; GIS